CIPP Evaluation of International Class towards World Class University - Afni, Rizky Nur; Ubaidillah, Aan Fardani (Proceedings Series of Educational Studies, 2025)
The International Class Program (ICP) is an educational initiative that integrates an international curriculum, emphasizing the use of global languages, international resources, and field practices with a global scope. Evaluation plays a crucial role in managing the program by identifying challenges, proposing solutions, and guiding improvements. It systematically measures the achievement of program objectives, assesses quality against established criteria, and provides essential data for informed decision-making. This study aims to evaluate the learning implementation and its impact on the department of Ali University, Malang, as part of its efforts to achieve World Class University status. Using the CIPP evaluation model, researchers analyzed the context, input, process, and product aspects of the program through interviews, observations, and documentation. The findings showed that the ICP in the department is functioning effectively, though the use of international languages, particularly English, remains suboptimal. A key issue is the insufficient number of qualified lecturers to support the program. Despite these challenges, the ICP has had a positive impact, as evidenced by improved student learning outcomes and notable achievements in both academic and non-academic areas.